In standard form, the equation of a parabola is:
![ax^2+bx+c=y](https://img.qammunity.org/2023/formulas/mathematics/college/k56ye74l4rpcwvco02icid3cdok8rb3et2.png)
We have three points, and we evaluate this equation for these three points. For the point (1, -3):
![a+b+c=-3\ldots(1)](https://img.qammunity.org/2023/formulas/mathematics/college/fe5okbgiexis3wkkhiyw3rv8g5n7m5ybfg.png)
For (3, 9):
![9a+3b+c=9\ldots(2)](https://img.qammunity.org/2023/formulas/mathematics/college/6ioi35ddcqbk4njix0iy2hf26n98k5t94f.png)
For (4, 18):
![16a+4b+c=18\ldots(3)](https://img.qammunity.org/2023/formulas/mathematics/college/pu5yjdoh6e3s2ixcpgixodbjpw3s3duxd0.png)
Now, subtracting (1) from (2) and (3):
![\begin{gathered} \begin{cases}8a+2b=12 \\ 15a+3b=21\end{cases} \\ \\ \Rightarrow\begin{cases}4a+b=6\ldots(4) \\ 5a+b=7\ldots(5)\end{cases} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/53xnwblsjm151wa39ookczrbnrd23htw26.png)
Solving this system of equations leads to ((5) - (4)):
![\begin{gathered} 5a+b-4a-b=7-6 \\ \Rightarrow a=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/txgtmydx9htlewhg15gl50cnjuygoayiox.png)
Now, using this result in (4):
![\begin{gathered} 4\cdot1+b=6 \\ \Rightarrow b=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u15ubm6bnyoauohiz0fb2761a414e58dqa.png)
Finally, using a and b in (1):
![\begin{gathered} 1+2+c=-3 \\ \Rightarrow c=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/z8vqxs9f5tac690d9wf8g9ficd0k92qg3k.png)
The standard form of the parabola passing through the three points (1,-3), (3,9), and (4,18) is:
![y=x^2+2x-6](https://img.qammunity.org/2023/formulas/mathematics/college/ehfl2b9f168tun643sgpaqncp4vonn4559.png)